The Search for Biomarkers and Treatments in Chagas Disease: Insights From TGF-Beta Studies and Immunogenetics - Ferreira, Roberto Rodrigues; Waghabi, Mariana Caldas; Bailly, Sabine; Feige, Jean-Jacques; Hasslocher-Moreno, Alejandro M.; Saraiva, Roberto M.; Araujo-Jorge, Tania C. (Frontiers in Cellular and Infection Microbiology, 2022)
The anti-inflammatory cytokine transforming growth factor beta (TGF-β) plays an important role in Chagas disease (CD), a potentially life-threatening illness caused by Trypanosoma cruzi. In this review we revisited clinical studies in CD patients combined with in vitro and in vivo experiments, presenting three main sections: an overview of epidemiological, economic, and clinical aspects of CD and the need for new biomarkers and treatment; a brief panorama of TGF-β roles and its intracellular signaling pathways, and an update of what is known about TGF-β and Chagas disease. In in vitro assays, TGF-β increases during T. cruzi infection and modulates heart cells invasion by the parasite fostering its intracellular parasite cycle. TGF-β modulates host immune response and inflammation, increases heart fibrosis, stimulates remodeling, and slows heart conduction via gap junction modulation. TGF-β signaling inhibitors reverts these effects opening a promising therapeutic approach in pre-clinical studies. CD patients with higher TGF-β1 serum level show a worse clinical outcome, implicating a predictive value of serum TGF-β as a surrogate biomarker of clinical relevance. Moreover, pre-clinical studies in chronic T. cruzi infected mice proved that inhibition of TGF-β pathway improved several cardiac electric parameters, reversed the loss of connexin-43 enriched intercellular plaques, reduced fibrosis of the cardiac tissue, restored GATA-6 and Tbox-5 transcription, supporting cardiac recovery. Finally, TGF-β polymorphisms indicate that CD immunogenetics is at the base of this phenomenon. We searched in a Brazilian population five single-nucleotide polymorphisms (-800 G>A rs1800468, -509 C>T rs1800469, +10 T>C rs1800470, +25 G>C rs1800471, and +263 C>T rs1800472), showing that CD patients frequently express the TGF-β1 gene genotypes CT and TT at position -509, as compared to noninfected persons; similar results were observed with genotypes TC and CC at codon +10 of the TGF-β1 gene, leading to the conclusion that 509 C>T and +10 T>C TGF-β1 polymorphisms are associated with Chagas disease susceptibility. Studies in genetically different populations susceptible to CD will help to gather new insights and encourage the use of TGF-β as a CD biomarker.